Effect of Waves’ Parameters on the Efficiency of a Pontoon Floating Breakwater Using Computational Fluid Dynamics - براءة عليا; امال حيدر (Latakia University Journal -Engineering Sciences Series, 2024)
Floating breakwaters are one of the coastal protection structures. They are usually designed to protect port’s facilities and beaches. The often-used type of breakwaters is the conventional type such as the rubble mound type. However, climate change that causes tidal variations and sea level rise, as well as unsuitable soil conditions to receive large structural loads will be more economical if using floating breakwaters. In this study, a numerical simulation will be conducted using FLOW 3D software. The aim of this research is to study the effect of wave parameters (height and length) on the efficiency of a pontoon floating breakwater.